Penerapan Sanksi Hukum Terhadap Kejahatan Geng Motor Yang Dilakukan Anak di Bawah Umur - Rahman, Abdul (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2016)
Raids motorcycle gang lately has become popular by security forces incooperation with other relevant institutions, because they feel frustrated and worried by the increasing criminal acts committed by motorcycle gang by various modes crimes. The perpetrators are generally aged 14 to 21 years. Various parties should be able to know clearly and accurately about the factors that cause child a felony. Need to look for what the background so that the children are likely to engage in criminal acts. If causality is known, must be followed up with efforts to find a way out right so as to counteract the occurrence of crimes committed by children.